Hybrid disinfection of sewage effluent—A comparative study of three secondary treatment plants of Jaipur, India. Issue 44 (19th September 2016) - Verma, Kavita; Shukla, Priyesh; Gupta, A.B.; Gupta, K.D.
Abstract: Chlorination is one of the most widely used methods to disinfect wastewater, despite innumerable objections raised due to the resultant by-products. Any attempt to reduce the dosage of chlorine can be very useful in lowering the concentration of the disinfection by-products, many of which have been reported to be carcinogenic. This study examines the microbiological characterization of secondary treated sewage from three different sewage treatment plants based on different unit processes, namely activated sludge process, moving bed biofilm reactor and rotating biological contractor. The study also assesses the efficacy of using chlorine on major coliform species in order to achieve the objective of bringing the effluent to the desired standard for total coliform count (TCC) of 1, 000 per 100 mL. The results indicate that 5 parts per million (ppm) chlorine dose (CD) was able to attain the TCC standard, if the counts for Serratia/Hafnia species were ignored. These species offered high resistance to chlorination due to which excessive overall doses were required to confirm to TCC standard. The chlorinated samples were further subjected to ultraviolet (UV-C) disinfection, the results of which can be employed to design a hybrid disinfection strategy with chlorination at a relatively low CD as the first step for removing bulk of the coliform population, followed by another process to which Serratia/Hafnia are susceptible. This can not only reduce the CD and thereby the by-products of chlorination but also bring down the overall cost of disinfection.